Arbutin determination in medicinal plants and creams - W. Thongchai (2018)
A simple flow injection (FI) manifold with spectrophotometric detection was fabricated and tested for arbutin determination. It is based on the measurement of a red-coloured product at 514 nm formed by the complexation reaction between arbutin and 4-aminoantipyrine (4-AP) in the presence of hexacyanoferrate (III) in an alkaline medium. On injecting 300 μL standard solutions at various concentrations of arbutin into the FI system under optimum conditions, a linear calibration graph over the range of 1.0-30.0 μg mL-1arbutin was established. It is expressed by the regression equation y = 0.2188 ± 0.0036x + 0.1019 ± 0.0366 (r2= 0.9990, n = 5). The detection limit (3σ) and the limit of quantitation (10σ) were 0.04 μg mL-1and 0.13 μg mL-1, respectively. The RSD of intraday and interday precisions were found to be 1.2-1.4% and 1.7-2.7%, respectively. The method was successfully applied in the determination of arbutin in four selected fruits and three commercial whitening cream extracts with the mean recoveries of the added arbutin over the range of 96.2-99.0%. No interference effects from some common excipients used in commercial whitening creams were observed. The method is simple, rapid, selective, accurate, reproducible and relatively inexpensive. © 2009 Society of Cosmetic Scientists and the Société Française de Cosmétologie.